2016
DOI: 10.17511/ijpr.2016.i06.06
|View full text |Cite
|
Sign up to set email alerts
|

Accidental poisoning its magnitude and implications in children

Abstract: Background: Paucity of data due to underreporting of accidental poisoning (AP) poses obstacle in assessing the trend, incidence, and mortality in pediatric population. Objective: Estimating the magnitude and assessing the pattern of AP in children was the primary objective. Describing the affected age group, common agents, and assessment of clinical features were the secondary objectives. Materials & Methods: Children aged 1month-12years with history of AP were included; those with allergic reactions to plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Negligence of parents and caretakers may also be a contributing factor. [33][34][35] Poisoning among preschool or toddler age groups is primarily unintentional or accidental. In adolescents, it is mostly of suicidal nature.…”
Section: Discussionmentioning
confidence: 99%
“…Negligence of parents and caretakers may also be a contributing factor. [33][34][35] Poisoning among preschool or toddler age groups is primarily unintentional or accidental. In adolescents, it is mostly of suicidal nature.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in Saudi Arabia, Sri Lanka, Brazil, and China, paracetamol and anti-pyretic were the most dominant causes of medication poisoning [ 20 , 31 - 33 ]. In South Korea, when comparing before and after Covid-19, it was found that antipyretics/nonsteroidal anti-inflammatory drugs and respiratory drugs were more common in the pre-Covid-19 group, whereas iron/vitamins, cardiovascular drugs, and hormones were more common in the post-Covid-19 group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%